Fat-soluble Vitamin Deficiencies and Inflammatory Bowel Disease: Systematic Review and Meta-Analysis. Issue 10 (November 2017) - Fabisiak, Natalia; Fabisiak, Adam; Watala, Cezary; Fichna, Jakub
Abstract : Background: Vitamin deficiency is frequently associated with inflammatory bowel disease (IBD). Supplementation of vitamins could thus serve as an adjunctive therapy. The present meta-analysis reviews the deficiencies and alterations in serum fat-soluble vitamins (A, D, E, and K) reported in IBD patients. Materials and Methods: PubMed database search was performed to identify all primary studies up to January 2015 that evaluated the serum concentrations of fat-soluble vitamin levels in IBD patients compared with healthy individuals. We estimated pooled mean differences between groups and estimated their relations with some compounding variables (age, disease duration, C-reactive protein, albumin), using a meta-regression analysis. Results: Nineteen case-control studies met selection criteria. In patients with Crohn's disease (CD), vitamin A, D, E, K status was lower than in controls [D=212 μg/L.92; 95% confidence interval (CI), 95.36-330.48 μg/L, P =0.0002; D=6.97 nmol/L, 95% CI, 1.61-12.32 nmol/L, P =0.01; D=4.72 μmol/L, 95% CI, 1.60-7.84 μmol/L, P =0.003; D=1.46 ng/mL, 95% CI, 0.48-2.43 ng/mL, P =0.003, respectively]. Patients with ulcerative colitis had lower levels of vitamin A than controls (D=223.22 μg/L, 95% CI, 44.32-402.12 μg/L, P =0.01). Patients suffering from CD for a longer time had lower levels of vitamins A (95% CI=7.1-67.58 y, P =0.02) and K (95% CI, 0.09-0.71 y, P =0.02). Meta-regression analysis demonstrated statistically significant associations between the levels of inflammatory biomarkers: C-reactive protein ( P =0.03, 95% CI, −9.74 to −0.6 mgl/L) and albumin ( P =0.0003, 95% CI, 402.76-1361.98 g/dL), and vitamin A status in CD patients. Conclusion: Our meta-analysis shows that the levels of fat-soluble vitamins are generally lower in patients with inflammatory bowel diseases and their supplementation is undoubtedly indicated.